Wacana Introver dalam Konten TikTok (Analisis Wacana Kritis Teun A Van Dijk) - Adhitya Candra Kirana (Universitas Merdeka Malang, 2023)
Introvert stereotypes that has developed in society construct them as flawed personalities. This negative perception is closely linked to the “Extrovert Ideal” which places a higher value on extroverted personalities. Over time, introvert stereotypes have continued to evolve, especially with the widespread of social media usage, like fTikTok. This research aim to explain how introvert discourse developed in TikTok content. This research used a qualitative research methods and a critical discourse analysis technique ofTeun A. van Dijk. The research reveals that there is a discourse of resistance against introvert stereotypes such as introvert as quiet, shy, reclusive, and antisocial individuals, also the stereotype of introvert as an illness. The resistance against introvert streotypes manifest in three ways, satirical comedy, raising social awaress, and asserting introverts self-expression on social media.